Micro-scaled products development via microforming : deformation behaviours, processes, tooling and its realization - Fu, Ming Wang; Chan, Wai Lun (Springer Series in Advanced Manufacturing, 2014)
'Micro-scaled Products Development via Microforming' presents state-of-the-art research on microforming processes, and focuses on the development of micro-scaled metallic parts via microforming processes. Microforming refers to the fabrication of microparts via micro-scaled plastic deformation and  presents a promising micromanufacturing process. When compared to other  micromanufacturing processes, microforming offers advantages such as high productivity and good mechanical properties of the deformed microparts. This book provides extensive and informative illustrations, tables and photos in order to convey this information clearly and directly to readers. Although the knowledge of macroforming processes is abundant and widely used in industry, microparts cannot be developed by leveraging existing knowledge of macroforming because the size effect presents a barrier to this knowledge transfer. Therefore systematic knowledge of microforming needs to be developed. In tandem with product miniaturization, the demand on microparts has been increased for their wide applications in many industries, including automotive, bio-medical, aerospace and consumer electronics industries. Micromanufacturing technologies have thus become more and more important. This book is intended for postgraduates, manufacturing engineers and professionals working in the areas of manufacturing and materials processing.